Diversity of Gill Cichlidogyrus spp. (Monopisthocotylean) Infecting Coptodon zillii (Gervais, 1848) from Lake Naivasha, Kenya - Nehemiah Mogoi Rindoria (Polytechnic)
Monopisthocotyleans of the genus Cichlidogyrus are ectoparasites which infest on skin, fins and gills of most teleosts in both capture fisheries and aquaculture. These parasites are often unnoticed, yet they cause damages to the organs they affect thereby increasing susceptibility of the fish to secondary infections. A total of fifty specimens of the introduced Redbelly tilapia Coptodon zillii (Gervais, 1848) were collected between November 2014 and April 2015 from Lake Naivasha, Kenya, and studied with the aim of collecting and identifying the gill monopisthocotyleans. Standard methods of parasitological examination were used in the identification of gill monopisthocotyla species. The collected monogeneans were preserved in 4% formalin for morphometric analysis. Seven Cichlidogyrus species were identified from the gills based on morphometric features of the opisthaptor and copulatory organs using identification keys. These include: Cichlidogyrus sclerosus Paperna & Thurston, 1969; C. tilapiae Paperna, 1960; Cichlidogyrus digitatus Dossou, 1982; Cichlidogyrus aegypticus Ergens, 1981; Cichlidogyrus vexus Pariselle & Euzet, 1995; Cichlidogyrus arthracanthus Paperna, 1960, and Cichlidogyrus yanni Pariselle & Euzet, 1996. The C. digitatus was the most dominant with a prevalence of 42% among the other monopisthocotyleans on C. zillii in the lake. These monopisthocotyleans form the first biogeographical record of their occurrence on C. zillii in Lake Naivasha, Kenya.